2014
DOI: 10.1038/srep07350
|View full text |Cite
|
Sign up to set email alerts
|

Contrast normalization in colour vision: the effect of luminance contrast on colour contrast detection

Abstract: While contrast normalization is well known to occur in luminance vision between overlaid achromatic contrasts, and in colour vision between overlaid colour contrasts, it is unknown whether it transfers between colour and luminance contrast. Here we investigate whether contrast detection in colour vision can be normalized by achromatic contrast, or whether this is a selective process driven only by colour contrast. We use a method of cross-orientation masking, in which colour detection is masked by cross-orient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 43 publications
(88 reference statements)
0
3
0
Order By: Relevance
“…The results from the present study have revealed a new type of interaction between suprathreshold color and luminance contrast in the context of binocular vision. We mentioned earlier that Mullen et al (2014) found strong dichoptic masking of colored target gratings by orthogonally oriented luminance gratings. It seems likely that the dichoptic masking of color contrast by luminance contrast revealed by Mullen et al, and the promotion of dichoptic saturation averaging by matched luminance contrast in the present study are mediated by similar mechanisms.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The results from the present study have revealed a new type of interaction between suprathreshold color and luminance contrast in the context of binocular vision. We mentioned earlier that Mullen et al (2014) found strong dichoptic masking of colored target gratings by orthogonally oriented luminance gratings. It seems likely that the dichoptic masking of color contrast by luminance contrast revealed by Mullen et al, and the promotion of dichoptic saturation averaging by matched luminance contrast in the present study are mediated by similar mechanisms.…”
Section: Discussionmentioning
confidence: 77%
“…If the matched and unmatched features therefore need to be similar along dimensions other than the one defining the mismatch in order for the matched features to reduce the interocular suppression between the unmatched features, one might suppose that matched luminance contrasts would have little impact on the appearance of unmatched color saturations. However, Mullen, Kim, and Gheiratmand (2014) have found that a luminance grating in one eye strongly masks an orthogonally oriented color grating in the other eye, suggesting that color and luminance contrast strongly interact in dichoptic vision. We might therefore expect matched luminance contrasts to reduce the interocular suppression between unmatched color saturations, causing them to average.…”
Section: Introductionmentioning
confidence: 99%
“…When characterized using detection thresholds, these mechanisms appear to be independent, showing a lack of subthreshold summation ( Mullen & Sankeralli, 1998 ). Above threshold, these pathways interact in a variety of ways, including the enhancement of luminance sensitivity by chromatic contrast, and masking effects between color channels ( Chen, Foley, & Brainard, 2000 ; Cole, Stromeyer, & Kronauer, 1990 ; DeValois & Switkes, 1983 ; Mullen, Kim, & Gheiratmand, 2014 ; Shooner & Mullen, 2020 ; Switkes et al, 1988 ). With these interactions not yet fully understood, it is of interest to search for any differences in how chromatic and achromatic contrast are processed above threshold.…”
Section: Discussionmentioning
confidence: 99%